Voluntary Disclosures of Indian Microfinance Institutions - Arpita Sharma; Shailesh Rastogi (Australasian Accounting, Business and Finance Journal, 2022)
The microfinance sector is growing at an astonishing rate in India. Reserve Bank of India, from time to time, comes up with a lot of directions to maintain transparency and governance in the microfinance sector. The current study focuses on the voluntary disclosure (VD) of the Non-Banking Financial Companies- Microfinance Institutions in India. The study constructs an unweighted index to measure the VD scores of the firms. The study also estimates the technical efficiency of the firms in meeting dual objectives of social and financial efficiency of the microfinance institutions. The empirical testing derived the association of the VD score and the efficiency from the data sourced from 2015 to 2019. The findings suggest a negative association between VD and efficiency. The study's major contribution is the type of VD disclosed by the firms. Finding also suggests that firms consider discretionary disclosure a wasteful activity. The dual performance is low but shows a gradual increase. The study is relevant for the policymakers and managers to check the disclosure strategy and the patterns of these firms, which mainly depend on the donors for raising funds for their sustainability.
Keywords: Voluntary Disclosure; Non- Banking Financial Companies- Micro financial Institutions; Data Envelopment Analysis; Panel regression; Efficiency estimation